(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper explores the effectiveness of counter-productive work behaviors in improving the work experiences of non-standard workers at a multinational organization in Zimbabwe. This exploratory qualitative study involved ten research participants who varied in age, sexual category, work experience, and academic qualification. The participants engaged in semi-structured interviews, providing data on the effectiveness of deviant work behaviors to enhance the experiences of non-standard workers. The findings of the current study show that the work experiences of a majority of non-standard workers improved by engaging in counter-productive work behaviors (CWBs). CWBs improved the financial stability, reduced work related stress, and restored distributive justice and equity of most non-standard workers at the case multinational organization in Zimbabwe. Conversely, this study also found that engaging in counter-productive work behaviors amounts to gross misconduct and criminal nuisance, which have negative consequences and can result in dismissal and arrest. The study recommends that to reduce counter-productive work behaviors, organizations should conduct personality-based integrity tests during the recruitment and selection process. Organizations should also understand reasons why non-standard workers engage in deviant work behaviors and develop appropriate intervention strategies to monitor and control them.